2016
DOI: 10.1177/1049732316648114
|View full text |Cite
|
Sign up to set email alerts
|

Picture This

Abstract: An increasing number of high-functioning stroke survivors are present with minimal functional impairments and are often discharged with reduced access to community reintegration. Our objectives were to explore the lived experience of high-functioning stroke survivors and to identify gaps in community and rehabilitation services. Photovoice was used with five high-functioning stroke survivors to photo-document their experiences. A modified inductive thematic analysis was used, and meanings behind the photograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…To orient the research team to a reflective and detailed analysis of each co-researcher’s life experience (Maratos et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…To orient the research team to a reflective and detailed analysis of each co-researcher’s life experience (Maratos et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Stroke is one of the main causes of adult disability worldwide, with the greatest health consequences coming from a variety of physical, cognitive and emotional long-term impairments [1, 2]. Medically advanced acute care therapy [3] and modern rehabilitation after stroke [2] have increased the number of community dwelling persons with stroke [4], and in Sweden around 75% of stroke patients are discharged to their homes [5]. Stroke consequences are complex [6], and qualitative research has shown that in a long-term perspective, many individuals after stroke feel unsupported and abandoned [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of people living with stroke, means higher demands for appropriate long-term rehabilitation services, and community reintegration programs that are evidence based [17]. As research participants are the sole authorities of knowledge about their life, qualitative research becomes grounded in subjects that are meaningful to those it concerns [4, 12, 18]. Photovoice gives participants the opportunity to photograph their identified subjects or environments, and to further discuss them in a group [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations